2021
DOI: 10.1186/s12879-021-07011-9
|View full text |Cite
|
Sign up to set email alerts
|

Cholera outbreak caused by drinking unprotected well water contaminated with faeces from an open storm water drainage: Kampala City, Uganda, January 2019

Abstract: Background Kampala city slums, with one million dwellers living in poor sanitary conditions, frequently experience cholera outbreaks. On 6 January 2019, Rubaga Division notified the Uganda Ministry of Health of a suspected cholera outbreak in Sembule village. We investigated to identify the source and mode of transmission, and recommended evidence-based interventions. Methods We defined a suspected case as onset of profuse, painless, acute watery d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…This observation is quite similar in countries where V. cholerae thrives. For instance, a fishing community in Uganda practices open defecation leading to cholera outbreaks [53] or discharges pit latrines into open drainage channels during heavy rains, contaminating well water, which also results in cholera outbreaks [54].…”
Section: Discussionmentioning
confidence: 99%
“…This observation is quite similar in countries where V. cholerae thrives. For instance, a fishing community in Uganda practices open defecation leading to cholera outbreaks [53] or discharges pit latrines into open drainage channels during heavy rains, contaminating well water, which also results in cholera outbreaks [54].…”
Section: Discussionmentioning
confidence: 99%
“…The source of drinking water can be linked to various infectious diseases, as it was previously shown that groundwater was associated with possible enteric virus infections [ 68 ]. Importantly, a previous study from Uganda showed that contaminated water from an unprotected well was linked to cholera outbreak reported in 2019 in Sembule village [ 69 ]. Water source contamination has been reported among the most common risk factors for cholera outbreaks worldwide [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater is a crucial resource 1 that is increasingly endangered by various forms of contamination. 2 In this context, microorganisms, such as E. coli, 3 V. cholera, 4 or Salmonella 5 are responsible for severe health issues. Water treatment is of paramount importance to prevent outbreaks of waterborne diseases.…”
Section: Introductionmentioning
confidence: 99%